Potential of Nano-Ionic Copper Doped Activated Carbon as Adsorbent in Leachate Treatment. (2019) - Adam, N.H.; Yusoff, M.S.; N. A. Bakar, S.; Aziz, H.A.; Halim, H.
Abstract: In this study, nano-ionic copper doped oil palm frond activated carbon ( n -OPFAC) was prepared. The impregnation of ortho-phosphoric acid (H3 PO4 ) and oxidation methods were employed to determine the potential of n -OPFAC through chemical oxygen demand (COD) and colour adsorption in semi aerobic leachate. Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX) analysis was used in determining the changes of pores and chemical element on the surface of activated carbon (AC) in different conditions. AC from oil palm frond was impregnated with H3 PO4 for 1 hour in ratio of 1:3 before heating in muffle furnace. Preliminary studies revealed that maximum iodine number of 987mg/g was attained at temperature 400°C and 1 hour heating time. The doped activated carbon with nano-ionic copper was obtained by 1:2 ratio (w/w) in similar to heating temperature and time. Batch adsorption experiment was conducted at room temperature with initial dosage of 0.8g, constant shaking speed (200rpm) for duration of 15 to 75 minutes. The incorporation of n -OPFAC resulted in the highest adsorption percentage of COD and colour, which is 82% at 45 minutes and 57% at 60 minutes, respectively. Elemental study shows that oxygen (O) content increased from 14.91% to 16.76% in n -OPFAC. The presence of oxygenated functional groups on the surface of n -OPFAC increases the adsorption capacity in COD and colour removal. It also noted as potential adsorbent in future study.